2021
DOI: 10.1186/s13046-021-01836-7
|View full text |Cite
|
Sign up to set email alerts
|

A specific tRNA half, 5’tiRNA-His-GTG, responds to hypoxia via the HIF1α/ANG axis and promotes colorectal cancer progression by regulating LATS2

Abstract: Background Currently, tRNA-derived small RNAs (tsRNAs) are recognized as a novel and potential type of non-coding RNAs (ncRNAs), which participate in various cellular processes and play an essential role in cancer progression. However, tsRNAs involvement in colorectal cancer (CRC) progression remains unclear. Methods Sequencing analyses were performed to explore the tsRNAs with differential expression in CRC. Gain- and loss-of functions of 5’tiRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 62 publications
1
77
0
1
Order By: Relevance
“…Its stable structure and high expression in body fluids make it relatively easy to detect, which makes it possible to become a new potential biomarker for tumors. Currently, most studies on tsRNAs have described the effects on proliferation, invasion, and migration of tumor cells and the mechanisms involved in hypoxia and epithelial to mesenchymal transformation (EMT) ( 10 , 21 , 51 , 52 ). However, there are few studies on whether tsRNAs can be used as a biomarker for tumors ( 18 , 24 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its stable structure and high expression in body fluids make it relatively easy to detect, which makes it possible to become a new potential biomarker for tumors. Currently, most studies on tsRNAs have described the effects on proliferation, invasion, and migration of tumor cells and the mechanisms involved in hypoxia and epithelial to mesenchymal transformation (EMT) ( 10 , 21 , 51 , 52 ). However, there are few studies on whether tsRNAs can be used as a biomarker for tumors ( 18 , 24 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…have revealed the expression pro le of tsRNAs in human colorectal cancer (CRC) specimens via sequencing analyses, and identi ed a speci c tsRNA derived from the internal of mature tRNA-His-GTG, 5'tiRNA-His-GTG (its base sequence is GCCGTGATCGTATAGTGGTTAGTACTCTGCGTTGT), which is up-regulated in CRC tissues [9]. Then, in vitro and in vivo experiments have revealed that inhibition of 5'tiRNA-His-GTG suppressed cancer cell proliferation and colony formation, induced cell apoptosis, and affected tumor growth in nude mice, these indicate that 5'tiRNA-His-GTG may act an oncogenic role in the progression of colorectal cancers [9]. In breast cancer, Mo et.al.…”
Section: Discussionmentioning
confidence: 99%
“…have identi ed the new class of tsRNAs derived from tRNA(Glu), tRNA(Asp), tRNA(Gly), and tRNA(Tyr) through hypoxic stress induction, this tsRNA fragments can bind and displace the 3'UTRs of YBX1 gene, which encoded a RNA-binding protein, then suppress the stability of multiple oncogenic transcripts such as EIF4EBP1 and AKT1, results in tumor-suppressive and metastasissuppressive activity in breast cancers [10]. Furthermore, in colorectal cancer cells, the upregulated 5'tiRNA-His-GTG is found to directly target LATS2, which is a key component of the hippo signaling pathway, and inhibits cell proliferation and promotes cell apoptosis by regulating YAP protein activity [9]. Our bioinformatics analyses displayed the interaction relationship of tRFdb-3013a/b and their predicted target genes, and found tRFdb-3013a/b could bind the 3'UTR of ST3GAL1, which is highly expressed in colon adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent efforts attempted to classify and tabulate the tsRNAs that were being discovered in some higher organisms into a curated repository, and structured the tRFdb database [8]. Several studies have linked the tsRNAs to different human cancers, including colorectal [9], liver, and breast cancer [10], etc. Growing evidences demonstrated that many tsRNAs were differentially expressed in the tissues of multiple cancer patients, these dysregulated tsRNA fragments might serve as potential candidates for diagnostic and prognostic biomarkers, and even contribute to various biological processes of cancer development and progression [11].…”
Section: Introductionmentioning
confidence: 99%